Evaluasi User Experience Platform Video Communication dengan User Experience Questionaire (UEQ) - Chatrine Sylvia; Angela Angela; Fandi Halim (STMIK Budi Darma, 2021)
The learning from home (home-based learning) and working from home (work from home) policy which has been going on for more than 1 year since March 2020 after being set by the Minister of Education and Culture (Kemendikbud) has brought many changes in the way to work and study for the academic community, especially students and lecturers. This is also felt by the academic community at STMIK Mikroskil, especially in Information Systems study program who changes their learning from offline to online by utilize various available application platforms such as Microsoft Teams and the Zoom application, especially for its video conferencing features as audio-visual media. With the use of both communication platforms in online learning activities, it is necessary to evaluate its user experience as information to support decision making in order to improve learning management and academic activities in university environment. However, this evaluation activity has never been carried out for the two applications that being used. This study aims to measure the user experience of Microsoft Teams and the Zoom application, especially for its video conference to support the lecturers and students in Information Systems Study Program at STMIK Mikroskil. This measurement is intended to predict and compare the ability of technology elements in the form of user experience of those two applications through an analytical study by applying the User Experience Questionnaire (UEQ) method. The target respondents are lecturers and students, especially in the Information Systems study program in the STMIK Mikroskil environment. The results showed that the comparison of the Microsoft Teams means value was superior to the Zoom application. Therefore, Microsoft Teams is a video conferencing and communication platform that is preferred by students and academics of the STMIK Mikroskil Information Systems study program compared to the Zoom application